2020
DOI: 10.3389/fpsyg.2020.579322
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Effects of Antecedents on Continuance Intention to Gather Food Safety Information on Websites

Abstract: Virtual community websites are one of the applications that provide a platform for people with common interests to extend their social relations in social media. With the proliferation of food safety incidents in recent years, social media has often been a major channel for public engagement in risk communication because of its social networking and immediate interaction. To understand the users’ needs and satisfaction, this study proposed a model to develop and evaluate the antecedents of continuance intentio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…van der Heijden ( 2004) proposed his research result regarding hedonic-motivation system (HMS) by adding joy in the technology acceptance model (TAM) as a mediator between perceived ease of use and behavioral intention to use. Prior research indicated the influence of perceived usefulness on behavioral intention (e.g., Chen et al, 2009Chen et al, , 2013Tsai et al, 2020). Moreover, empirical evidence also supported the relationship between perceived usefulness and purchase intention (e.g., Jamal and Sharifuddin, 2015;Moslehpour et al, 2018).…”
Section: Hedonic-motivation System Adoption Modelmentioning
confidence: 80%
“…van der Heijden ( 2004) proposed his research result regarding hedonic-motivation system (HMS) by adding joy in the technology acceptance model (TAM) as a mediator between perceived ease of use and behavioral intention to use. Prior research indicated the influence of perceived usefulness on behavioral intention (e.g., Chen et al, 2009Chen et al, , 2013Tsai et al, 2020). Moreover, empirical evidence also supported the relationship between perceived usefulness and purchase intention (e.g., Jamal and Sharifuddin, 2015;Moslehpour et al, 2018).…”
Section: Hedonic-motivation System Adoption Modelmentioning
confidence: 80%
“…Since, the AVE was 0.430 and composite reliability was 0.815 for relatedness satisfaction, we consider convergent validity as satisfactory. Moreover, the square root of AVE for each construct was larger than the correlation coefficients among the constructs, indicating sufficient discriminant validity ( Fornell and Larcker, 1981 ; Tsai et al, 2020 ).…”
Section: Methodsmentioning
confidence: 97%
“…Different countries have different levels of development of the live football online platforms, while users in other countries have different payment behaviors. Future studies should expand the effective range of samples and the quantity with a wider geographical area (Tsai et al, 2020;Carranza et al, 2021).…”
Section: Discussionmentioning
confidence: 99%